Democratic Republic of the Congo : Joint Staff Assessment of the Interim Poverty Reduction Strategy Paper Preparation Status Report. (IMF Staff Country Reports; Country Report ;, 2004)
The attached Joint Staff Assessment (JSA) of the Interim Poverty Reduction Strategy Paper (I-PRSP) Preparation Status Report for the Democratic Republic of the Congo reviews progress with respect to the implementation of the PRSP. The report appropriately points to the continuing progress in the implementation of the I-PRSP, especially the restoration of peace, the strengthening of governance, and the improvement in economic management for pro-poor growth. Progress in the production of monthly budget execution reports and in improving the government accounting framework is good, despite some delays.